Performance Appraisal : Past, present and the way forward - Rusli, Ahmad (UNIMAS Publisher, 2019)
Organisations are now facing various possibilities, new development and fragile market place to remain competitive in the era of ICT. Competition becomes stiff, critical dan unpredictable therefore in need of powerful strategies to handle it. Employers and employees as the most important parties in an organisation always seeking aspirations for a harmonious relationship, avoiding all conflicts and looking forward to better work-life balance. Both have different targets where the former look at numbers and reputation, the latter dream of a fairly measured work performance. Without an effective, efficient and proper ways of handling performance appraisal system, it shall result in chaos for the organisation. This will lead to job dissatisfaction in the form of complaints of unfairness, job absenteeism, low motivation, less productivity, early retirement, and other problems, hence will negatively impact the organisation in the future. This book gives emphasis on the past, present and the way forward of handling the most sensitive human resource management topic, which is employees appraisal. This book offers contemporary ways of managing the appraisal system with the ultimate aims of maximising employees' potential and enhancing organisation's status.